SOSIALISASI PENTINGNYA KETERLIBATAN EMOSI DALAM PENGAMBILAN KEPUTUSAN - Kenny Richelling (LPPM Universitas Bina Bangsa, 2023)
Emotional Influence on Decision Making. In an economic environment, decision-making is an important part of determining whether a person or organization will receive an advantage or disadvantage for each choice they make. Often, decision making is not only based on economic factors, but also psychological factors, one of which is the emotional state. A person's emotional state often influences the decision making or choices of a person or leader in the organization. Sometimes decisions taken within their emotional influence, do not produce positive results. In this literature study, the author wants to discuss the influence of a person's emotions on their decision making.